Tetraoxygenated xanthones and biflavanoids from the twigs of Garcinia merguensis - Trisuwan K. (2014)
One new tetraoxygenated xanthone, merguensinone (1), along with one known xanthone, 1,5,6-trihydroxy-2-prenyl-6′,6′-dimethyl-2H- pyrano(2′,3′:3,4)xanthone (2) and five known biflavanoids, (-)-GB-1a (3), (-)-GB-2a (4), (+)-morelloflavone (5), (+)-volkensiflavone (6), and amentoflavone (7) were isolated from the methanol extract from the twigs of Garcinia merguensis. Their antibacterial activity against the standard Staphylococcus aureus ATCC 25923 and methicillin-resistant S. aureus and antioxidation activity with DPPH assay were examined. © 2013 Phytochemical Society of Europe.